International Legal Responses To Iran’s Nuclear Ambitions and Human Rights Violations: A Study Of Economic Sanctions - Fajar, Rizky Nur; Sutrisno, Andri (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
This study analyzes the international legal response to Iran's nuclear ambitions and human rights violations, focusing on the economic sanctions imposed by the United Nations, the United States, and the European Union. The research raises a key question about the effectiveness of sanctions in halting Iran's nuclear program and their impact on human rights violations. Using a qualitative research approach and doctrinal legal analysis of international resolutions, treaties, and reports, the study assesses the consequences of these sanctions. The findings indicate that, although the sanctions have had a significant impact on Iran's economy, leading to a decline in foreign investment and GDP, they have not been effective in limiting Iran's nuclear efforts. Moreover, the sanctions have worsened human rights violations, particularly related to food security, healthcare, and political repression. The study concludes that sanctions alone have limitations in encouraging compliance, and therefore a more integrated approach is needed, involving diplomacy, multilateral engagement, and more targeted sanctions to address both nuclear and human rights issues